Tips and Tricks in Thoracic Surgery (Springer London, 2018)
Thoracic surgery is a high-risk speciality and requires attention to detail. This book, compiled by expert surgeons from around the world, offers pearls of wisdom on how to improve the surgical outcome and how to reduce unnecessary complications. The book is designed so that it covers all common thoracic operations in both adults and children as well as dealing with much rarer indications. It includes a discussion on the complications of surgery and provides specific tips on how to avoid intra-operative and postoperative complications. Tips and Tricks in Thoracic Surgery is a fully illustrated, comprehensive text aimed at qualified and trainee thoracic surgeons.